MicroRNA‐495 regulates starvation‐induced autophagy by targeting ATG3. Issue 6 (4th March 2016) - Li, Wen; Yang, Yue; Hou, Xiaoyan; Zhuang, Haixia; Wu, Zijun; Li, Zhiyi; Guo, Runmin; Chen, Hao; Lin, Chunxia; Zhong, Wangtao; Chen, Yusen; Wu, Keng; et al.
Abstract : The functions of some essential autophagy genes are regulated by microRNAs. However, an ATG3‐modulating microRNA has never been reported. Here we show that the transcription of miR‐495 negatively correlates with the translation of ATG3 under nutrient‐deprived or rapamycin‐treated conditions. miR‐495 targets ATG3 and regulates its protein levels under starvation conditions. miR‐495 also inhibits starvation‐induced autophagy by decreasing the number of autophagosomes and by preventing LC3‐I‐to‐LC3‐II transition and P62 degradation. These processes are reversed by the overexpression of an endogenous miR‐495 inhibitor. Re‐expression of Atg3 without miR‐495 response elements restores miR‐495‐inhibited autophagy. miR‐495 sustains cell viability under starvation conditions but has no effect under hypoxia. Moreover, miR‐495 inhibits etoposide‐induced cell death. In conclusion, miR‐495 is involved in starvation‐induced autophagy by regulating Atg3. Abstract :